2019
DOI: 10.31246/mjn-2018-0139
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors affecting food insecurity among university students in Pahang, Malaysia

Abstract: Introduction: Food insecurity exists whenever people are unable to access sufficient food at all times for an active and healthy life. University students are a potentially vulnerable group of people to face food insecurity. This study aimed to identify the prevalence and determinants of food insecurity among a population of university students in Kuantan, in the state of Pahang. Methods: Food security status was identified using the United States Adult Food Security Survey Module (USAFSSM). Factors, which inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…An analysis of the data derived revealed that most of the students constituting 57.6% indicated that they were food insecure. This finding agrees with a study in Pahang, Malaysia on prevalence and factors contributing to food insecurity among university students which found that 54% of the students were food insecure, 33% were low food secure and 21% were very low food secure [11]. It was further found that 56.4% of the students afforded only two meals per day and only a minority could afford three meals per day.…”
Section: Discussion Of the Findings 41 Discussion Quantitative Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…An analysis of the data derived revealed that most of the students constituting 57.6% indicated that they were food insecure. This finding agrees with a study in Pahang, Malaysia on prevalence and factors contributing to food insecurity among university students which found that 54% of the students were food insecure, 33% were low food secure and 21% were very low food secure [11]. It was further found that 56.4% of the students afforded only two meals per day and only a minority could afford three meals per day.…”
Section: Discussion Of the Findings 41 Discussion Quantitative Findingssupporting
confidence: 90%
“…This also resonates with a study South-Eastern US on the student specific factors which include increased cost of housing and tuition, low income, inadequate financial resources, poor food management skills, increased reliance on borrowed finances and ineligibility for food assistance programmes [17]. Further, a study on prevalence and factors contributing to food insecurity among university students in Pakistan, found that time management, expenditure on books, income of guardians, type of scholarship, academic programmes and miscellaneous items contributed to food insecurity [11].…”
Section: Discussion Of the Findings 41 Discussion Quantitative Findingsmentioning
confidence: 99%
“…In a study by Bakar et al (2019), an important association was found between food security status with financial availability, time constraint, scholarship, academic program and parent income (2019) among university students in Pahang, Malaysia. According to the report, one of the students of the Allied Health Sciences programs, which also had the highest number of food deprived students, was the largest proportion of beneficiaries of PTPTN loans.…”
Section: Malaysiamentioning
confidence: 99%
“…University participation is vital in ensuring food security because college students are a group that is highly impacted by food insecurity, with prevalence estimates on Malaysian campuses ranging between 22% and 69.4% (Razak et al , 2014 ; Abu Bakar et al , 2019 ; Izwan Syafiq et al , 2019 ; Rajikan et al , 2019 ; Jamil et al , 2020 ). Food insecurity among university students can negatively impact their academic performance, physical and mental health, and food choices.…”
Section: Introductionmentioning
confidence: 99%